2020
DOI: 10.1177/0846537120914263
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tissue Plasminogen Activator in Abdominal Abscesses in Children—A Single-Center Randomized Control Trial

Abstract: Purpose: To establish the efficacy of once-per-day intracavitary tissue plasminogen activator (tPA) in the treatment of pediatric intra-abdominal abscesses. Methods: A single-center prospective, double-blinded, randomized controlled trial of the use of intracavitary tPA in abdominal abscesses in children. Patients were randomized to either tPA-treatment or saline-treatment groups. Primary outcome was drainage catheter dwell (hours). Secondary outcomes were length of hospital stay, times to discharge, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Gibson CR et al, 2021 [61] Randomized controlled trial, with a sample size of 56 pediatric patients.…”
Section: Study Study Design Aim Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gibson CR et al, 2021 [61] Randomized controlled trial, with a sample size of 56 pediatric patients.…”
Section: Study Study Design Aim Resultsmentioning
confidence: 99%
“…For more complex collections, intracavitary tissue plasminogen activator (tPA) with a normal saline solution has been suggested to facilitate drainage; this therapy can be performed as needed or on a set regimen [ 59 , 60 ]. However, a recent study by Gibson et al found no benefits of tPA over a regular saline flush in terms of shorter catheter dwell time, procedure time to discharge, or time to resolution [ 61 ].…”
Section: Image-guided Percutaneous Abscess Drainagementioning
confidence: 99%
See 1 more Smart Citation